1985
DOI: 10.1083/jcb.100.4.1091
|View full text |Cite
|
Sign up to set email alerts
|

Structural organization of interphase 3T3 fibroblasts studied by total internal reflection fluorescence microscopy.

Abstract: We studied the laminar organization of 3T3 fibroblast cells growing on glass slides by use of total internal reflection illumination to excite fluorescence emission (TIRF) from labeled molecules and stained cellular compartments that are very close to the cell-substrate contact region. Mitochondria, distant from the contact regions and stained with the watersoluble cationic dye, diI-C3-(3), fluoresced only as the glass/cytoplasm critical angle was approached. A similar result was obtained when the nuclei were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
82
0
1

Year Published

1986
1986
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(88 citation statements)
references
References 47 publications
5
82
0
1
Order By: Relevance
“…Cell locomotion leads to redistribution of fluorescence to pseudopods or to the lamellipodium and uropod. These cellular sites are responsible for adherence of PMNs and fibroblasts to substrates (23)(24)(25)(26)(27). Therefore, accumulation of histamine ligand-receptor complexes at these sites may sterically exclude membrane components participating in adhesion or decrease adhesion through the action of a second messenger such as cAMP.…”
Section: Discussionmentioning
confidence: 99%
“…Cell locomotion leads to redistribution of fluorescence to pseudopods or to the lamellipodium and uropod. These cellular sites are responsible for adherence of PMNs and fibroblasts to substrates (23)(24)(25)(26)(27). Therefore, accumulation of histamine ligand-receptor complexes at these sites may sterically exclude membrane components participating in adhesion or decrease adhesion through the action of a second messenger such as cAMP.…”
Section: Discussionmentioning
confidence: 99%
“…Nutrition is supplied during the experiment from the incubator through the chip system. In the literature (Lanni et al 1985;Bretschneider et al 2004;Weisswange et al 2005;Partridge and Marcantonio 2006;Manneville 2006), there are many examples of the use of EF in combination with TIRF for measuring global and membrane-specific events. However, in the present study, EF setup was used only for illuminating the whole field to locate the cells before and/or after the TIRF images were recorded.…”
Section: Quantification Of Cellular Contact and Lift-off 387mentioning
confidence: 99%
“…Gingell et al (1987) developed a rigorous electromagnetic theory of total internal reflection and applied it to the establishment of a quantitative basis for mapping cell-substratum topography. The TIRF technique has been used in biological studies, such as cell-substrate contacts, vesicle fusion, and single-molecule observation (Lanni et al 1985;Thompson and Lagerholm 1987;Wang and Axelrod 1994;Burmeister et al 1998;Toomre and Manstein 2001;Li et al 2004;Bretschneider et al 2004;Manneville 2006;Young and Marcantonio 2007). Lanni et al (1985) observed fibroblast cells growing on glass slides and Fuhr et al (1998) reported the observation of cell adhesion and migration by using different microscopic techniques, including TIRF.…”
Section: Introductionmentioning
confidence: 99%
“…Using interference reflection microscopy (Izzard & Lochner 1976), electron microscopy (Chen & Singer 1982) and total internal reflection fluorescence (TIRF) microscopy (Lanni et al, 1985;Truskey et al, 1992), it has been revealed that distance between the VPM and the substratum is 10-20 nm at FAs and  100 nm in other regions. If one considers the size of an integrin molecule (8  12 nm for an extracellular headpiece and 18 nm for flexible legs (Weise et al, 1992)), the gap between the VPM and the substratum outside FAs is much larger than the reach of the molecule.…”
Section: Introductionmentioning
confidence: 99%